Geodetic monitoring of deformations of the earth's surface and the main gas pipeline in the area affected by mining operations - Kolesnik, N.; Kozhemiako, M. (Land Management, Cadastre and Land Monitoring, 2024)
Abstract. The importance of the task of calculating and analyzing the displacements and deformations of the earth's surface for monitoring the state of objects located on the earth's surface within the influence of mining operations is substantiated. Studies have been conducted that indicate that the actual values of earth surface displacements and deformations differ significantly from the calculated values determined by standard methods. Today, when developing measures to protect objects on the earth's surface, a regulatory methodology is used that applies an overload coefficient. However, it does not make it possible to determine the actual range of the variation of subsidence and deformation of the earth's surface. The authors of the article substantiate the design of an observation station for geodetic measurements of earth surface displacements and deformations of the main gas pipeline, which is being undermining by the Geroyev Kosmosa mine of DTEK Pavlohradvuhillya. An observation station was laid and instrumental observations were made using a GNSS receiver from Leica Geosystem. According to the normative methodology, the expected and calculated subsidence and deformation of the earth's surface within the influence of the 960th longwall were calculated for certain mining and geological conditions. The results obtained by the authors during the natural measurements confirm the variation of subsidence and deformation along the main sections of the trough. It is proposed to take the obtained results into account when choosing the means of protection of the main gas pipeline.Key words: displacement and deformation of the earth's surface, geodetic monitoring, observation station, GNSS observation, natural measurements, trough.
Keywords: displacement and deformation of the earth's surface; geodetic monitoring; observation station; GNSS observation; natural measurements; trough